Are there any association between polycistic ovary syndrome and congenital abnormalities of Müllerian ducts - Tubić - Pavlović, Aleksandra; Radović - Janošević, Dragana; Petrić, Aleksandra; Stefanović, Milan (Vojnosanitetski pregled, 2014)
Background/Aim. There are many specificities of merital infertility and sometimes surprising connections between some thinks with no connections at first sight. Examinations of these patients imply diagnostic actions such as the blood basal hormone sample, doing hysterosalpingography, ultrahysterosonography, ultrasound examinations, and sometimes laparoscopy and hysteroscopy if there are necessary. The aim of the study was to determine the characteristics of the connection between policystic ovary (PCO) syndrome (Sy) and congenital Müllerian ducts abnormalities. Methods. This study included 356 patients treated in the period from January 1, to December 31, 2009, in the Department of Infertility of the Clinic for Obstetrics and Gynecology in Niš, Serbia. Exclusion criteria were no myoma, ovary cysts, tubal and male factors of infertility. Results. A total of 180 patients were divided into 3 groups: the group I with PCO sy, the group II with uterine congenital malformation and the group III with a combination of these disorders. The middle age of patients was 29.6 ± 4.8, body mass index (BMI) was 26.1 ± 4,8 kg/m2 the middle thicknes of endometrium was 5.2 + 2.7 mm, and there were no significant differences between the examined groups. There were no significant among in a number of miscarriages in the examined groups. We found that PCO Sy and congenital abnormalities of Müllerian ducts were conjoint in 30% of examined patients. Conclusion. Conjoined PCO Sy and congenital abnormalities of Müllerian ducts do not result in a higher number of misscarriages than only either PCO Sy or abnormalities of Müllerian ducts. It is important to check BMI, basal level of follicle stimulating hormone and number of antral follicles because the induction protocol and concentracion of inductors depends on these characteristics, thus, the succsessful cycles and pregnancy.